Natural Killer Cells Utilize both Perforin and Gamma Interferon To Regulate Murine Cytomegalovirus Infection in the Spleen and Liver - Loh, Joy (American Society for Microbiology, 2005)
Natural killer (NK) cells are critical for innate regulation of the acute phase of murine cytomegalovirus (MCMV) infection and have been reported to utilize perforin (Pfp)- and gamma interferon (IFN-γ)-dependent effector mechanisms in an organ-specific manner to regulate MCMV infection in the spleen and liver. In this study, we further examined the roles of NK cells, Pfp, and IFN-γ in innate immunity to MCMV infection. With the recently described NK cell-deficient (NKD) mouse, we confirmed previous findings that NK cells, but not NKT cells, are required for control of the acute phase of MCMV infection in spleen and liver cells. Interestingly, we found that Pfp and IFN-γ are each important for regulating MCMV replication in both the spleen and the liver. Moreover, NK cells can regulate MCMV infection in the spleens and livers of Pfp(−/−) mice in a Pfp-independent manner and can use an IFN-γ-independent mechanism to control MCMV infection in IFN-γ(−/−) mice. Thus, contrary to previous reports, NK cells utilize both Pfp and IFN-γ to control MCMV infection in the spleen and liver.